Dynamic background on formation, evolution, and later reformation of the Late Paleozoic–Early Mesozoic Basin in Songliao and its significance for hydrocarbon exploration - Song, Lijun; Ruan, Yongqi; Sun, Yonghe; Xie, Fenquan; Li, Junlong; Yuan, Yulong (Frontiers in Earth Science, 2023)
Located on the Songnen block of the Northeast Asia block group, the Songliao Basin is sandwiched by three major plates in Siberia, North China, and the Pacific Ocean. The recognition of the basin's properties and the dynamic processes of formation, evolution, and late reformation of the Late Paleozoic–Early Mesozoic Basin (LP-EMB), which has suffered from intense multi-stage, and various types of late reformation, are always controversial. On the basis of previous research on the regional tectonic geological background, combined with petrochemical and chronological data from core samples and seismic data, the attributes, evolution process, and late reformation of the LP-EMB and its dynamic environments have been deeply analyzed. Since the Late Paleozoic, it has successively experienced the development of Late Hercynian to Early–Middle Indosinian rifts and subsequent multi-stage superimposed transformation stages, which can be divided into the near-north-trending thrust reformation in the Late Indosinian, the near-west-trending thrust reformation in the Early Yanshanian, the differential extensional reformation in the early Late Yanshanian, the strike-slip shearing and deep burial reformation in the middle Late Yanshanian, and the strike-slip compression fold transformation in the late Late Yanshanian to the early Himalayan. The formation of the LP-EMB was mainly controlled by back-arc extension caused by the subduction and retreat of the paleo-Pacific Plate and partly by the closure of the Paleo-Asian Ocean between the North China Plate and the Northeast Asia micro-block group. The later reformation stages were closely related to the collision extrusion, strike-slip activity, and deep mantle activity caused by either the relative convergence movement between Songnen and other micro-blocks in the Northeast China micro-block group or by the remote collision effect of the Northeast China micro-block group and the surrounding plates. The inner fault zone (body), which was formed by multi-phase fault cutting, and the top weathering and denudation unconformity surface, are potential sites of hydrocarbon accumulation, from which natural gas has been transported along the fault and fracture belt into the weathering crust and the inner fracture zone in the Upper Paleozoic–Lower Mesozoic (UP-LM). This study significantly expands our knowledge of the tectonic evolution and gas exploration of the Songliao Basin.